Assessment of the quality and readability of online information on autopsy for the general public: a cross-sectional analysis. Issue 5 (30th May 2019) - Hanley, Brian; Brown, Philip; O'Neill, Shane; Osborn, Michael
Abstract : Objectives: Hospital (consented) autopsy rates have dropped precipitously in recent decades. Online medical information is now a common resource used by the general public. Given clinician reluctance to request hospital postmortem examinations, we assessed whether healthcare users have access to high quality, readable autopsy information online. Design: A cross-sectional analysis of 400 webpages. Readability was determined using the Flesch-Kincaid score, grade level and Coleman-Liau Index. Authorship, DISCERN score and Journal of the American Medical Association (JAMA) criteria were applied by two independent observers. Health on the net code of conduct (HON-code) certification was also assessed. Sixty-five webpages were included in the final analysis. Results: The overall quality was poor (mean DISCERN=38.1/80, 28.8% did not fulfil a single JAMA criterion and only 10.6% were HON-code certified). Quality scores were significantly different across author types, with scientific and health-portal websites scoring highest by DISCERN (analysis of variance (ANOVA), F=5.447, p<0.001) and JAMA (Kruskal-Wallis, p<0.001) criteria. HON-code certified sites were associated with higher JAMA (Mann-Whitney U, p<0.001) and DISCERN (t-test, t=3.5, p=0.001) scores. The most frequent author type was government (27.3%) which performed lower than average on DISCERN scores (ANOVA, F=5.447, p<0.001). Just 5% (3/65) were at or below the recommended eight grade reading level (aged 13–15 years). Conclusions: Although there were occasional high quality web articles containing autopsy information, these were diluted by irrelevant and low quality sites, set at an inappropriately high reading level. Given the paucity of high quality articles, healthcare providers should familiarise themselves with the best resources and direct the public accordingly.